Design wizards for contemporary political poster design elements - Fadel Mourad, Rawan; Taha Yassin, Iman (Al-Adab Journal, 2020)
Political posters are a powerful motivating tool and a deep visual and mental message of attraction for the individual and the public, and a phenomenon of a social and psychological nature, and it is considered one of the propaganda tools that influence all times, in war and peace, elections, demonstrations and social media